Islamic Radicalism, Terrorism and Anti-Pancasila: Examining the Roots of Radicalism and the Anti-Pancasila Movement - Imamuddin Imamuddin; Tio Adinata (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
This study aims to analyze the relationship between radical Islamic ideology, acts of terrorism, and the emergence of anti-Pancasila movements in Indonesia. The phenomenon of radicalism is often the root cause of terrorist acts that threaten not only physical security but also the ideological stability of the state. Using qualitative methods through literature review and descriptive analysis, this study examines the triggering factors of radicalism, ranging from narrow religious understanding, global political influence, to socio-economic dissatisfaction. The results of the study indicate that anti-Pancasila movements often use religious narratives to delegitimize the national consensus, which, if left unchecked, can develop into systematic acts of terrorism. This study concludes that strengthening religious moderation and revitalizing Pancasila values in education and public spaces are crucial steps to stem the infiltration of radical ideology in society.